Statistical Analysis of High-Power Impulse Magnetron Sputtering Parameters on the Growth and Composition of AlN Thin Films - Azman, Zulkifli; Nayan, Nafarizal; Abu Bakar, Ahmad Shuhaimi; Sahari, Norain; Bakri, Anis Suhaili; Mohd Rofei Mat Hussin; Ahmad, Mohd Yazid (International Journal of Integrated Engineering, 2025)
This study presents an experimental investigation of Aluminium Nitride (AlN) thin film deposition using High-Power Impulse Magnetron Sputtering (HiPIMS). The main goal is to investigate the significant effect of HiPIMS sputtering parameters on the growth and chemical composition of the AlN thin film. A Design of Experiments (DoE) approach is used to conduct interaction studies among the common sputtering parameters, such as sputtering power, working pressure, and the Argon (Ar) to Nitrogen (N2) ratio. The 2k factorial design is specifically used in this case. The main plot effect demonstrates that the sputtering power was the most significant factor in AlN thin film growth, whereas the growth was inversely proportional to working pressure. The working pressure had a significant impact on the oxygen concentration of the AlN thin films. It was discovered that lower working pressure and higher HiPIMS power were chosen to obtain a balanced stoichiometry with less oxygen concentration. The strong preferred (002) plane orientation of AlN on Silicon, Si (111) substrate produced a with the lowest oxygen content of 5.4% by weight. The results of this work will aid in understanding HiPIMS capabilities and in streamlining the deposition procedure to produce AlN thin films of better quality for usage in piezoelectric and optoelectronic applications.